Composición química de la madera de Juglans neotropica Diels y su relación con las propiedades químicas del suelo en un ecosistema forestal de la parroquia Valladolid, provincia de Zamora Chinchipe - Valverde Rodríguez, Jhuliana Xiomara (2020)
This study of chemical characterization of wood allows to know the contents of holocellulose, lignin, extracts and ash, produced during the development of an individual tree. The knowledge of the patterns of variation of the chemical components of the wood within the same species makes possible a greater and better use of this forest resource. It is frequent to find studies on the relationship of the chemical characteristics of the soil with the growth rate and the accumulation of biomass; however, studies on the effect of the soil on the chemical properties of wood of tropical species of great ecological importance are scarce. In this sense, this research aimed to evaluate the chemical composition of the wood of J. neotropica and its relationship with the chemical properties of the soil, in a forest ecosystem of the parish of Valladolid. For this purpose, methodologies and standardized protocols (TAPPI) were applied; five individual trees of J. neotropica from the parish of Valladolid were selected, from which a branch was obtained, to later extract wood flour, and with it determine the percentage of extractive agents, ash, lignin and holocellulose present. To determine the chemical properties of the soil, three soil samples were obtained for each tree around a radius of two meters. These were processed and the content of pH, nitrogen and phosphorus available was obtained. In the analysis of the data of the wood composition and the chemical properties of the soil, the non-parametric test of Kruskal-Wallis was used and to evaluate the relationship between the variables mentioned, the correlation coefficient with the non-parametric test of Spearman was determined. The results indicate that the wood of J. neotropica, had holocellulose in a 78.9 %, 13.39 % of lignin, 5.76 % of extractive and 1.94 % of ash. The soil where the sampled individuals developed was acidic with an average pH of 5.21 and has high levels of nitrogen (159.39 ppm) and phosphorus (57.33 ppm). The greater or lesser concentration of chemical components present in the wood of J. neotropica is influenced by the availability of macro elements in the soil. High levels of nitrogen decrease the lignin content and increase the holocellulose content, while high levels of phosphorus decrease the extractive content, however, the pH and ash have no relation to the components and properties analyzed. It is necessary to make complementary studies on the chemical composition of the wood J. neotropica and its relation with the chemical properties of the ground; in different ecosystems and taking samples of trees of diverse ages, with the purpose of establishing the optimal conditions for the development and better advantage of this species. Keywords: Extractives, ash, lignin, holocellulose, pH, nitrogen and phosphorus